PS02.148: ENDOSCOPIC MANAGEMENT OF GASTRO-BRONCHIAL FISTULA FOLLOWING 2-STAGE OESOPHAGECTOMY USING OVER-THE-SCOPE-CLIP (OTSC): CASE SERIES. (14th September 2018) - Ying Tan, Chih; Arkar Kyaw, Htet; Lorenzi, Bruno; Charalampopoulos, Alex; Venkatesh Jayanthi, Naga; Tang, Cheuk
Abstract: Background: Post-oesophagectomy gastro-bronchial fistula (GBF) has significant morbidity and mortality. Management of GBF remains non-standardized due its rarity and limited available evidence. Re-operation and surgical repair has been the main approach. More recently, multimodal endoscopic treatment is gaining popularity as primary treatment option due to its relatively non-invasiveness, increasing evidence of success rate and reduced morbidity. We present a case series of GBF managed endoscopically using over-the-scope-clip (OTSC). Methods: A dedicated, prospective and contemporaneous regional Upper GI cancer database was searched to identify GBF from January 2015 to December 2017. Clinical notes and investigation images of identified cases were analysed. Results: Three patients developed post-oesophagectomy GBF during study period. Mean age of patients was 53. Mean time of GBF diagnosis was 233 days (range: 20–608). Two patients had endoscopic stent placement prior to OTSC application. Primary technical success was achieved in all patients. No adverse events were reported. Two patients had complete healing of GBF and mean healing time was 15 days (range: 6–24). One patient who had significant co-morbidities (peripheral arterial disease, diabetes, hepatitis C, rheumatoid arthritis and heavy smoker) developed persistent leak of GBF and died from cardiac event. Conclusion: GBF and its surgical treatment are associated with a high morbidity and mortality. We present this case series where two out of three patients with GBF were successfully treated with this modality. Endoscopic therapy incorporating OTSC placement is a feasible option in management of post-oesophagectomy GBF. Further studies are required to understand and establish its role in treatment algorithm of post-oesophagectomy GBF. Disclosure: All authors have declared no conflicts of interest.